O grotesco na montanha em contos de Miguel Torga - Silva Neto, Floriano Esteves da (2014)
The present work proposes point and discuss the expression and the sense of the grotesque country tales by Miguel Torga (1907-1995). The books analyzed were Bichos, Contos da montanha e Novos contos da montanha. The research of the theme is made on the basis of the deductive method, in the bibliographical research and literary analysis. To develop the reading of the tales under grotesque prism were used theoretical studies by Victor Hugo (2007) and Wolfgang Kayser (2009), in addition to the contributions of Anatol Rosenfeeld (1996) and Philip Thomson (1972). The analysis of short narratives by Miguel Torga evidences the complex social relations, revealing the grotesque universe that emerges from them.